Analytical model for the prediction of the elastic response of curved T-stubs - Mudrov, Andrej; Jaspart, Jean-Pierre; Corman, Adrien; Šapalas, Antanas (Journal of Civil Engineering and Management, 2021)
Composite steel-concrete columns utilise the advantages of both materials, by combining high strength and ductility of steel with the compressive strength of the concrete. But the wide adaptation of composite structures is limited, mainly because of the lack of cheap and easy to construct connections, as many of which require costly and timeconsuming on-site welding, when circular concrete filled steel tubes (CFST) are adopted. New connections, like those incorporating the use of blind bolts and curved end-plates, may represent a valuable alternative. Such joints can be adapted to circular CFST to eliminate on-site welding, but they require the creation of new curved T-stub components. This paper proposes an analytical model for the evaluation of bolt forces in the curved T-stubs within the elastic range. The model is then validated against experimental results of joints between circular CFST columns and steel beams, with both preloaded and snug tightened bolts. Analytical model shows good agreement with experimental data, but needs further development to take into account the prying forces.